Determinants of Participation and Detection Rate of Colorectal Cancer From a Population-Based Screening Program in China - Zhang, Jiangong; Xu, Huifang; Zheng, Liyang; Yu, Juan; Chen, Qiong; Cao, Xiaoqin; Liu, Shuzheng; Jose Gonzalez, Maria; Guo, Lanwei; Sun, Xibin; Zhang, Shaokai; Qiao, Youlin (Frontiers in Oncology, 2020)
Colorectal cancer (CRC) screening has been widely implemented in Europe and the United States. However, there is little evidence of participation and diagnostic yields in population-based CRC screening in China. The participation rate and detection of colorectal lesions in this program were reported and related factors were explored. The analysis was conducted in the context of the Cancer Screening Program in Urban China, which recruited 282,377 eligible participants aged 40-74 years from 8 cities in Henan province from 2013 to 2019. 39,834 participants were evaluated to be high-risk for CRC by an established risk score system and were subsequently recommended for colonoscopy. Of 39,834 with high-risk for CRC, 7,454 subjects undertook colonoscopy (participation rate of 18.71%). We found that 50-64 years, high level of education, marriage, former smoking, current alcohol drinking, low levels dietary intake of vegetables, high levels dietary intake of processed meat, lack of physical activity, FOBT positive result, history of colonic polyp, history of colorectitis, and family history of CRC were associated with increased participation of colonoscopy screening. Overall, 17 CRC (0.23%), 95 advanced adenoma (1.27%), 478 non-advanced adenomas dysplasia (6.41%), 248 hyperplastic polyp (3.33%) and 910 other benign lesions (12.21%) were detected. Our findings will provide important references for designing effective population-based CRC screening strategies in the future. There was room for improvement regarding CRC screening yield given the relatively low participation rate.